Analisis Psikologi Sastra Dalam Novel Sin: God Hates The Sin, Not The Sinner Karya Faradita - Rahma, Amalia Nur; Hefni, Asnan; Setyawati, Meita (Adjektiva: Educational Languages and Literature Studies, 2021)
Novel is a work of fiction that tells the life of a character. Therefore, one of the important elements in the novel is the character. This study aims to describe the psychology of the main and additional characters in the SIN novel "God hates the sin, not the sinner" by Faradita. Literary psychology is a text analysis by considering the relevance and role of psychological studies. The psychological theory used is the theory of Behaviorism described by Skinner. This research is a type of qualitative research with descriptive method. The data source is in the form of dialogue and narration in the sin novel "god hates the sin, not the sinner". The research data are in the form of dialogues and narratives containing literary psychology. Data was collected using the read and note method. The novel's story begins with the meeting of Metta and Raga at an entertainment venue. Raga who saves Metta from his ex-lover's evil plan. Because of this meeting, Metta and Raga establish a relationship and there is a conflict between the two of them so that their relationship cannot be maintained. Based on data analysis, the research results obtained are the psychology of the main character, namely; 1) stimulus from the school environment, 2) family environment, and 3) friendship environment and 1) arrogant response, 2) not understanding other people's circumstances, and 3) difficulty regulating feelings. The two additional psychology characters are; 1) a stimulus from the family environment and 2) a friendly environment and 1) a response to feeling like a puppet of his father and 2) a sense of disapproval.